Factors Affecting Amputation in Patient with Diabetic Foot Ulcer at Sardjito General Hospital - Andreas Wahyu Wicaksono (Journal of Global Pharma Technology, 2020)
Background: Diabetic foot ulcer (DFU) can cause significant morbidity and need for surgical intervention due to the high prevalence of diabetic foot problems in general population. The incidence of DFU is 15% of all diabetic patients. Eighty-two percent (82 %) of DFU will lead to lower extremity amputation. Therefore, the factors that affecting the needs of distal limb amputation should be described for prevention and decrease the need of amputation and morbidity of the patients. Objective: The aim of this study is to determine factors affecting distal limb amputation in patient with DFU. Methods: The design of this study is retrospective cohort, using data of DFU patient treated surgically from January 2012 to September 2016. Socioeconomic factors, Blood profile, Diabetes Mellitus (DM) profile and Ankle Brachial Index (ABI) were collected. All the data were then analyzed using SPSS. Result: There were 119 patients were enrolled in this study. Thirty-nine patients (32.7%) had distal limb amputation. The amputation level was forefoot (34 patients, 87%), mid foot (2 patients, 5%), hind foot (2 patients, 5%) and Trans tibial (1 patient, 3%) amputation. This study showed that socioeconomics factors were not significantly correlated with distal limb amputations in patients with diabetic ulcer. The level of DLA was not affected by patient’s blood profile, DM profile and ABI. Conclusion: Decision to perform surgical intervention can not only rely on the laboratory profile and socioeconomic factors of the patients. Clinical judgement of the doctor and the patients' general conditions should also be considered.